Patient consent in emergency cardiovascular medicine: lessons from the ARREST trial in out-of-hospital cardiac arrest. (25th November 2020) - Perkins, A; Patterson, T; Evans, R; Clayton, T; Fothergill, R; Redwood, S
Abstract: Introduction: Randomised trials in emergency cardiovascular medicine are challenging but vital for improving patient care. Obtaining informed consent in such an environment is a particular issue and can be controversial. The ARREST trial is assessing whether out-of-hospital cardiac arrest patients without an obvious cause should be taken to a specialist heart centre or the closest emergency department in London, UK. This patient group presents specific difficulties: patients lack capacity to consent, presentation is unpredictable, care must not be delayed, and mortality rates can be >50%. Purpose: Within existing consent and methodological frameworks we aimed to design a randomised clinical trial to pragmatically, safely and ethically recruit cardiac arrest patients pre-hospital. Methods: During the set-up of ARREST we accessed the following sources of information: 1) ARREST research team; 2) cardiovascular patient groups; 3) researchers running similar trials; 4) regulatory bodies; and, 5) published literature on research in emergency contexts. The information that we collected guided the design of the trial with a focus on patient consent, documentation and follow-up. Results: The ARREST trial uses deferred consent with remote online randomisation to enrol patients without delaying care. To minimise the risk of bias, baseline and primary endpoint data are collected on patients who die or are discharged prior to consent. Remote follow-up using electronic health records reduces the burden on the patients and researchers. Full ethical approval was received in January 2018 and the first patient was enrolled in February 2018. ARREST is recruiting to target and is on track to finish within the projected timelines. Conclusions: Deferred consent has been key to the success of ARREST and patients have been receptive. However, further research into the experience of patients in emergency cardiovascular medicine trials using deferred consent is needed to better understand when it is an appropriate model. More broadly, there is a shortfall in high quality research in challenging environments such as emergency cardiovascular care. Innovation in consent methods and proportional research governance would facilitate higher quality research and benefit patient care. Funding Acknowledgement: Type of funding source: Foundation. Main funding source(s): British Heart Foundation